ADUBAÃ‡ÃƒO VERDE EM CULTIVO ORGÃ‚NICO DE HORTALIÃ‡AS - Ambrosano, Edmilson JosÃ©; Rossi, FabrÃcio; Tamiso, Luciano Grassi; Mello, Paulo CÃ©sar Tavares de; Schammass, Eliana Aparecida; Guirado, Nivaldo; Tessarioli Neto, JoÃ£o (REVISTA DE AGRICULTURA, 2015)
ADUBAÇÃO VERDE EM CULTIVO ORGÂNICO DE HORTALIÇAS